The impact of corporate social responsibility (CSR) on relationship quality in perspective of employees : A case study of ENCORP Berhad / Farah Najwa Asnan - Asnan, Farah Najwa (Faculty of Business Management, 2016)
In this emerging market economy with rapid advances of information and communication technology also includes globalization and liberalization, businesses in Malaysia are facing stiff challenges to maintain and survive in this competitive environment. One of the biggest challenges faced by most business is to fulfil the expectation of society of being responsible corporate citizens that will eventually have effect on long run profitability. Many company believes that corporate social responsibility (CSR) is the best action to be taken in order to be socially responsible towards society.